Official Languages and International Treaties- A Reading of Iraqi Treaties Ratification Law of 2016 - Ahmed, Sirwan Hamd; Ghareeb, Halmat Saadoon (Journal of Legal and Political Studies, 2021)
Our research topic entitled "official Languages and International Treaties - A Reading of the Iraqi Treaty Contract Law of 2015", revolves around the topic of the language of editing international treaties, so that it identifies legal problems related to the difference in the meaning of terms and verbal connotations between one language to another, and even within the framework of one language from one country to another, Or the difference in meaning between the time of the conclusion of the treaty and the time of its subsequent implementation, or the problems relating to the publication and interpretation of the treaty internally, and an indication of the effect of this problematic to the application of the treaty. The study mainly deals with the presentation and clarification of the position of the Iraqi Treaty Contract Law of 2015 related to the language of treaty editing and the translation of treaties edited in foreign languages in the event of Iraq’s regulation and publication in accordance with the Iraqi law of publication, and rules relating to its interpretation, and we have identified legal complaints and the most important weaknesses in the treaty contract law In order to achieve this, we followed the analytical method, and we have found through this research that the Iraqi Constitution Contracts Law of 2005 and the official Languages Law No. (7) of 2014 and the Publication Law in the official Gazette No. (78) for the year 2007 amended No. (34) of 2007 relating to official languages in Iraq. In the conclusion of the research, we suggested that the necessary amendments to the 2015 Treaty of Contracts Act should be made in order to harmonize with the 2005 Iraqi constitution and the laws in force regarding official languages and publishing rules in Iraqi facts.
Keywords: official Languages; International Treaties; legal problem; verbal connotations; 2015 Treaty of Contracts Act